Theory of Mind and Children's Trait Attributions about Average and Typically Stigmatized Peers. Issue 2 (9th June 2015) - Lapan, Candace; Boseovski, Janet J.
Abstract : Previous research indicates that children hold negative beliefs about peers with foreign accents, physical disabilities, and people who are obese. The current study examined skills associated with individual differences in children's social judgements about these typically stereotyped groups. Theory of mind, memory, and cognitive inhibition were assessed in 3‐ to 6‐year‐olds. Then, children were asked to make trait attributions and behavioural predictions about story characters' willingness to help a peer. Results indicated that better theory of mind skills were related to greater positive trait attributions and behavioural predictions about typically stereotyped characters. Younger children made fewer positive behavioural predictions as compared to older children, but both age groups made positive trait attributions. Overall, memory and inhibition had little to no influence on children's responses, although the results varied by story type. Copyright © 2015 John Wiley & Sons, Ltd.